Designing classical Dragonian offset dual-reflector antennas from combinations of prescribed geometric parameters. - Granet, Christophe (IEEE Antennas & propagation magazine.)
This paper proposes a simple procedure for the design of classical offset-Dragonian dual-reflector antennas from combinations of prescribed geometric parameters. This procedure has already been applied to classical Cassegrain and Gregorian antennas, and to classical displaced-axis Cassegrain and Gregorian antennas. We provide a list of 20 parameters from which the antenna system is fully characterized, but only five of these parameters need to be provided by the antenna designer, as the remaining 15 parameters can be derived in closed-form using the procedure described. We consider that the main reflector (MR) has a circular aperture, while the subreflector (SR) has an elliptical aperture